For a comment of Rossi Precerutti’s Entrebescar (1982) (inOpera Esercizi di lettura su testi contemporanei, 2024)
This paper previews a commented critical edition of Entrebescar (1982) by Roberto Rossi Precerutti. Nine poems from the first section of the book have been selected, and can be considered as an inner micro-series showing the relevance of Derrida’s concept of dissemination in the context of the collection. The commentary is accompanied by metric notes and (when present) variants. Thanks to the commentary, the ways in which a reader can deal with this type of poetry starting from its structure (thus, the metrics, prosody and syntax) will be clear, even when the general meaning of the poems should be regarded as open and undecidable.
Keywords: Rossi Precerutti; Entrebescar; Critical Edition; Commentary; Contemporary Poetry